Natural history of cardiac function in Duchenne and Becker muscular dystrophies on home mechanical ventilation - Fayssoil, Abdallah (Medicine (Baltimore), 2018)
Heart impairment is classical in dystrophinopathies and its management relies on medical drugs. Mechanical ventilation is used to treat respiratory failure, but can affect cardiac function. We aimed to investigate the natural history of cardiac function in patients with Duchenne (DMD) and Becker (BMD) muscular dystrophies on home mechanical ventilation (HMV). We reviewed the chart of DMD and BMD patients, followed in our institution, to obtain ventilation setting at HMV initiation and echocardiographic data at baseline and end follow up, as well as onset cardiac events and thoracic mechanical complication. We analyzed cumulative incidence of cardiac events as well as echocardiographic parameters evolution and its association with ventilation settings. We included 111 patients (101 DMD and 10 BMD). Median age was 21 years [18–26], median pulmonary vital capacity (VC) 15% of predicted [10–24]. All patients were on HMV and 46% ventilated using tracheostomy. After a median follow up of 6.3 years, we found a slight decrease of the left ventricular ejection fraction (LVEF) (45% at end follow up vs 50% at baseline P = .019) and a stabilization of the LV end diastolic diameter indexed (LVEDD indexed 29.4 mm/m(2) vs 30.7 mm/m(2) at end follow up, P = .17). Tidal volume (VT) level was inversely associated with the annual rate of the LVEF decline (r = −0.29, P = .025). Left atrium (LA) diameter decreased with mechanical ventilation (24 mm vs 20 mm, P = .039) and we found a reduction of systolic pulmonary pressure (35 mm Hg vs 25 mm Hg, P = .011). The cumulative incidence of cardiac events was 12.6%. Pneumothorax occurred in 4% of patients. Hypoxic arrest secondary to the presence of tracheal plugin occurred in 4% of patients with invasive ventilation. HMV is not harmful, decreases pulmonary pressure and may protect heart in dystrophinopathies, in addition with cardioprotective drugs. In patients with DMD and BMD on HMV, cumulative incidence of cardiac events remains moderate and incidence of pneumothorax is rare.